2000
DOI: 10.1007/s001050051212
|View full text |Cite
|
Sign up to set email alerts
|

Prästernales verruköses Karzinom

Abstract: Verrucous carcinomas represent rare, highly differentiated variants of squamous cell carcinoma. They preferentially develop on the oropharyngeal mucosa (Ackerman tumor), the urogenital mucosa (Buschke-Loewenstein tumors), and the soles of the feet (epitheliomata cuniculata). Various synonyma have been coined for these tumors. We report the uncommon occurrence of a large verrucous carcinoma on apparently uninvolved chest skin of a 79-year old patient. The tumor was excised radically. Complete extirpation was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Compared to oral, genitoanal, and palmoplantar verrucous carcinomas, cutaneous verrucous carcinomas arising elsewhere in skin as in our case are exceedingly rare. In our review of the literature published between 1981 and 2003, we found only 17 cases (summarized in Table 1) of verrucous carcinoma not localized in the classical regions 9,22 , 25,29–38 . Interestingly, most of them were located in the sacral or buttock region (10/17), 9,22 , 25,29–33 suggesting a potential relation to the verrucous carcinoma localized in the classical anogenital region.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to oral, genitoanal, and palmoplantar verrucous carcinomas, cutaneous verrucous carcinomas arising elsewhere in skin as in our case are exceedingly rare. In our review of the literature published between 1981 and 2003, we found only 17 cases (summarized in Table 1) of verrucous carcinoma not localized in the classical regions 9,22 , 25,29–38 . Interestingly, most of them were located in the sacral or buttock region (10/17), 9,22 , 25,29–33 suggesting a potential relation to the verrucous carcinoma localized in the classical anogenital region.…”
Section: Discussionmentioning
confidence: 91%
“…The incidence rate of GCA differs between countries; this is related either to histomorphological differentiation or the lack of epidemiological studies. GCA is more common in the penis than anogenital or mouth locations . The annual incidence of condyloma acuminatum is 1 per cent in the USA, the UK, Panama and Italy.…”
Section: Discussionmentioning
confidence: 99%
“…GCA is more common in the penis than anogenital or mouth locations. 57 The annual incidence of condyloma acuminatum is 1 per cent in the USA, the UK, Panama and Italy. In the last millennium 1.2 cases were published per year.…”
Section: Discussionmentioning
confidence: 99%